Role of imaging for eligibility and safety of a-NGF clinical trials - Roemer, Frank; Hochberg, Marc C.; Carrino, John A.; Kompel, Andrew J.; Diaz, Luis; Hayashi, Daichi; Crema, Michel D.; Guermazi, Ali (Therapeutic Advances in Musculoskeletal Disease, 2023)
Nerve growth factor (a-NGF) inhibitors have been developed for pain treatment including symptomatic osteoarthritis (OA) and have proven analgesic efficacy and improvement in functional outcomes in patients with OA. However, despite initial promising data, a-NGF clinical trials focusing on OA treatment had been suspended in 2010. Reasons were based on concerns regarding accelerated OA progression but were resumed in 2015 including detailed safety mitigation based on imaging. In 2021, an FDA advisory committee voted against approving tanezumab (one of the a-NGF compounds being evaluated) and declared that the risk evaluation and mitigation strategy was not sufficient to mitigate potential safety risks. Future clinical trials evaluating the efficacy of a-NGF or comparable molecules will need to define strict eligibility criteria and will have to include strategies to monitor safety closely. While disease-modifying effects are not the focus of a-NGF treatments, imaging plays an important role to evaluate eligibility of potential participants and to monitor safety during the course of these studies. Aim is to identify subjects with on-going safety findings at the time of inclusion, define those potential participants that are at increased risk for accelerated OA progression and to withdraw subjects from on-going studies in a timely fashion that exhibit imaging-confirmed structural safety events such as rapid progressive OA. OA efficacy- and a-NGF studies apply imaging for different purposes. In OA efficacy trials image acquisition and evaluation aims at maximizing sensitivity in order to capture structural effects between treated and non-treated participants in longitudinal fashion. In contrast, the aim of imaging in a-NGF trials is to enable detection of structural tissue alterations that either increase the risk of a negative outcome (eligibility) or may result in termination of treatment (safety).
CRIS-Team Scopus Importer:2023-07-07
Keywords: a-NGF; clinical trials; eligibility; MRI; nerve growth factor; osteoarthritis; radiography; safety